Pengaruh Kualitas Pelayanan Administrasi Terhadap Kepuasan Pasien Pengguna BPJS Kesehatan di RSUD Lubuk Basung Kabupaten Agam - Rindu Antika Sari; Armiati Armiati (Universitas Negeri Padang, 2019)
This study aims to explain the effect of service quality on patient satisfaction of health BPJS users in Lubuk Basung Hospital Agam District. The measurement of the quality dimension uses five dimensions of service quality consisting of tangibles, reliability, responsiveness, assurance, empathy. The research instrument used was a questionnaire distributed to 100 patients with BPJS Kesehatan using the chocran formula taken using accidental sampling techniques. Data collection techniques in this study are using questionnaires compiled using a Likert scale whose score is 1-5. To ensure that the instruments used in the study are tested for validity, and reliability testing. In the data analysis stage the influence of the quality of administrative services on patient satisfaction of BPJS Health users in Lubuk Basung Hospital Agam Regency was carried out descriptive analysis, and inductive analysis. Inductive analysis is a normality test, multicollinearity test, heterocedasticity test, and multiple regression analysis. Hypothesis test data used F test, t test, and test coefficient of determination (R2). the results of this study show the five service quality variables simultaneously have a positive and significant effect on patient satisfaction BPJPS Health users in RSUD lubuk basung. While the factors that predominantly influence patient satisfaction in Lubuk Basung Hospital are tangibles, responsiveness, assurance, and followed by emphaty variables, and reliability. Keyword: service quality, tangibles, reliability, responsiveness, assurance, emphaty, patient satisfaction